An inquiry into China and Russia strategic partnership from geopolitical perspective - Ming-Xing, Yang; Li, Wang; Russel, Humprey Arnoldo («Մռավ» հրատ․)
Since the 1990s, China and Russia have come to forge strategic partnership which is seen as the counterbalance to the U.S. hegemony. Yet, the solidarity between the two largest powers in Eurasia is under the question since the Ukraine crisis has not only caused the unexpected impacts on the global energy and food security, but also the geopolitical dimensions now and beyond. What can Russia expect from China during the ongoing conflict, and how can China offer to Russia’s urgent needs as it has fought alone against the U.S.-led allies? Regarding the question if Beijing has tried “to keep its distance” from Moscow now or afterward, this study asserts that there is a profound historical logic for China-Russia relationship to reach where it is today. 1990-ական թվականներից սկսած Չինաստանի և Ռուսաստանի միջև սկսվեց ռազմավարական համագործակցության գործընթացը, որի նպատակը ԱՄՆ-ի հեգեմոնիայի դեմ հակակշռի ստեղծումն էր։ Երկու խոշորագույն եվրասիական ուժերի համերաշխությունը որոշակիորեն սասանվեց պայմանավորված ուկրաինական ճգնաժամի պատճառով, քանի որ այն հանգեցրեց անկանխատեսելի հետևանքների։ Ինչ կարող էր ակնկալել Ռուսաստանը Չինաստանից ԱՄՆ-ի գլխավորությամբ գործող դաշինքի դեմ միայնակ պայքարելու պայմաններում։
Keywords: History